2017
DOI: 10.1002/slct.201701702
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Porous Carbon Nanomaterials using Redox-Induced Low Molecular Weight Hydrogels and their Application as Supercapacitors

Abstract: We synthesized porous carbon and Fe3O4@porous carbon by direct carbonization of redox‐induced low‐molecular‐weight hydrogels. The transition of low‐molecular‐weight hydrogels to hard porous carbons was observed for the first time. Conversely, the transformation of sol to porous carbon was not successful. This suggests that connectivity was a crucial factor distinguishing the porous materials from others. More importantly, it provides a new synthetic route for fabrication of porous materials. The porous carbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…19,20,[23][24][25] The mesh size of hydrogels in the hydrated state can be determined by experimental techniques such as dynamic swelling, inverse size-exclusion chromatography, fluorescence recovery after photobleaching, probe diffusion by pulsed gradient spin-echo (PGSE) NMR, rheometry, and dynamic light scattering. 10,13,14,[26][27][28][29][30][31] In the present study, we used poly(NIPAM-co-AAc) as the model hydrogel and focused on the characterization of the mesh size by means of dynamic swelling, rheometry, and PGSE NMR. The difference between the mesh sizes obtained by these methods have been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20,[23][24][25] The mesh size of hydrogels in the hydrated state can be determined by experimental techniques such as dynamic swelling, inverse size-exclusion chromatography, fluorescence recovery after photobleaching, probe diffusion by pulsed gradient spin-echo (PGSE) NMR, rheometry, and dynamic light scattering. 10,13,14,[26][27][28][29][30][31] In the present study, we used poly(NIPAM-co-AAc) as the model hydrogel and focused on the characterization of the mesh size by means of dynamic swelling, rheometry, and PGSE NMR. The difference between the mesh sizes obtained by these methods have been established.…”
Section: Introductionmentioning
confidence: 99%
“…This polymer has been investigated in the forms of macroscopic hydrogels, films, micro‐ and nanoparticles . The mesh size of hydrogels in the hydrated state can be determined by experimental techniques such as dynamic swelling, inverse size‐exclusion chromatography, fluorescence recovery after photobleaching, probe diffusion by pulsed gradient spin‐echo (PGSE) NMR, rheometry, and dynamic light scattering . In the present study, we used poly(NIPAM‐ co ‐AAc) as the model hydrogel and focused on the characterization of the mesh size by means of dynamic swelling, rheometry, and PGSE NMR.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the semicircle diameter, the slope of the straight line, and the intercept of the x-axis separately stand for the charge transfer resistance (R ct ), the Warburg resistance (R w ), and equivalent series resistance (R s ), which reflects the charge transfer efficiency, the electrolyte ion diffusion or transport in the electrode, and the combination of the intrinsic resistance, electrolyte resistance, and interfacial contact resistance, respectively. 49 According to the Nyquist plots, it could be easily concluded that PBA/Ni-MOF-NS-12 h-Se displayed the steepest slope, the smallest semicircle diameter, and the smallest intercept, which indicated that it possessed the smallest R w , R ct , and R s ; and the R s and R ct values were calculated to be as low as 0.72 and 1.10 Ω (Table S2). In other words, PBA/Ni-MOF-NS-12 h-Se exhibited the lowest series resistance, highest charge transfer efficiency, and fastest electrolyte ion diffusion and transport among the prepared materials.…”
Section: Electrochemical Performance Of Pba/ni-mof-ns-x H-sementioning
confidence: 99%
“…In the case of LMWGs, adding a third component can be challenging since gelation is based on the fine balance of supramolecular interactions [5]. Preserving mechanical stability when the third component contains metal ions is even more difficult [18]. In this study, we present an investigation using the C18ADPA hydrogel as a robust drug carrier, even for drugs containing metal ions.…”
Section: Introductionmentioning
confidence: 99%